Extended-spectrum β-lactamase producing and Quinolone resistance Salmonella spp. in Dhaka city retail meat: an emerging public health concern of Bangladesh - Hossain, Muhammad Sazzad (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.